Contemporary prevalence and outcomes of rheumatic mitral valve surgery. Issue 7 (26th February 2022) - Hawkins, Robert B.; Strobel, Raymond J.; Mehaffey, J. Hunter; Quader, Mohammed A.; Joseph, Mark; Ailawadi, Gorav
Abstract: Objective: Rheumatic mitral valve disease is often viewed as a historic disease in North America with limited contemporary data. We hypothesized that rheumatic pathology remains common and has worse short‐term outcomes and higher resource utilization compared to other mitral valve pathologies. Method: All patients undergoing mitral valve repair or replacement (2011–2019) were extracted from a regional Society of Thoracic Surgeons database. Resource utilization metrics included inflation‐adjusted hospital costs. Patients were stratified by mitral valve pathology for univariate analysis. Result: Out of the 6625 mitral valve procedures, 835 (12.6%) were from rheumatic disease, a proportion that incrementally increased over time (+0.39% per year, p = .032). Among 19 hospitals, there was high variability in number of rheumatic mitral operations (median: 22, interquartile range [IQR]: 5–80) and rate of rheumatic repairs (median: 3%, IQR: 0%–6%). Rheumatic patients were younger (62 vs. 65, p < .0001), more often female (75% vs. 43%, p < .001) and with greater burden of heart failure, multi‐valve disease, and lung disease, but less coronary disease. There were no differences in operative mortality (5.2% vs. 5.0%, p = .85) or major morbidity (22.2% vs. 21.8%, p = .83). However, resource utilization was higher for rheumatic patients, including more frequent transfusions (43% vs. 39%, p = .012), longer ICU (73 vs. 64 h, p < .0001) and postoperative length of stay (8 vs. 7 days, p < .0001). Conclusions: Rheumatic mitral disease accounts for a meaningful (12%) and rising percentage of mitral valve operations in the region, with high variability among hospitals. Rheumatic mitral surgery yielded similar short‐term outcomes compared to nonrheumatic pathology, but required greater resource utilization.